REPRESENTATION OF FEMININE MEANING IN THE FILM WHEN LOVE IS TESTIMONIAL 1 (Semiotic Analysis by Charles Sander Pierce) - Namira Fitria; Parlin Harbet (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This research is a research that analyzes feminine values ​​in the religious cinema film When Love Tasbih 1. The formulation of the problem in this research is what are the signs and meanings that represent the values ​​of feminine meaning in the cinema film When Love Tasbih 1. This research uses data analysis, namely the meaning of symbols as a semiotic study. The method used is a qualitative descriptive method that shows the results of the research that emphasizes meaning more than generalization. The data in this study presents verbal texts and nonverbal texts. Verbal texts are in the form of writing and speaking, while nonverbal texts are in the form of images or settings contained in the film. As for the data collection technique, the researcher uses a note-taking technique in the form of (1) watching the film, (2) noting the things needed, (3) collecting (screen capture), (4) selecting, and (5) analyzing to obtain conclusions. The researcher uses Charles Sanders Pierce's semiotic study by focusing on the meaning of symbols as the data obtained. Furthermore, the data is analyzed to obtain the cultural values ​​contained in the film. Researchers found four images and narratives containing symbolic meanings related to feminine elements. Researchers discovered cultural values ​​in the form of the use of feminine words and symbols.